Proceedings of the 18th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2015
DOI: 10.1145/2675133.2675255
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Multi-Generational Crowd Workers in Social-Purpose Work

Abstract: Crowdsourcing for social goals (e.g., supporting public libraries or people with disabilities) is a promising area. However, little is known about how to develop active worker communities for such goals. First, we need reliable metrics for the workers' motivation. Second, the characteristics of senior crowd workers have rarely been studied, even though they often play a primary role in social-purpose work. This work introduces a four-quadrant worker motivation model for social-purpose crowdsourcing and describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 21 publications
0
34
0
1
Order By: Relevance
“…The designers of Incloodle [51] observed that neurotypical children often excluded neurodiverse children from play activities, and designed a cooperative photography application to enforce equal participation among participants to counter this hierarchy. Other work explored the potential of people with disabilities as employees [65] or volunteers [24,27], recognizing their unique strengths rather than immediately classifying people with disabilities as "less than." These papers begin the hard work of challenging hierarchies that devalue disabilities in favor of more abilities.…”
Section: Interdependence Can Challenge Ability-based Hierarchiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The designers of Incloodle [51] observed that neurotypical children often excluded neurodiverse children from play activities, and designed a cooperative photography application to enforce equal participation among participants to counter this hierarchy. Other work explored the potential of people with disabilities as employees [65] or volunteers [24,27], recognizing their unique strengths rather than immediately classifying people with disabilities as "less than." These papers begin the hard work of challenging hierarchies that devalue disabilities in favor of more abilities.…”
Section: Interdependence Can Challenge Ability-based Hierarchiesmentioning
confidence: 99%
“…We identify two threads of ongoing research related to crowd work and accessibility that may be usefully expanded through an interdependence framing. First, AT researchers [4,5,9,24,27,53,56,61,62,65] have explored crowd work as a means for people with disabilities to both receive assistance and find employment. Research regarding on-demand assistance focuses on systems, like VizWiz and RegionSpeak [4,6,62], that connect a disabled person in need of assistance with a remote crowd worker.…”
Section: Crowd Work and Interdependencementioning
confidence: 99%
See 1 more Smart Citation
“…In literature, it is difficult to demonstrate exactly the linkages and the causative pathways between mechanics, mediators and outcomes [30,31]. To illustrate this, a mechanic, designed as a badge or a reward, has been shown to impact intrinsic motivation to perform certain tasks [60]. However, exactly which psychological concepts or mediators contribute most impact and how they relate to each other remain unanswered.…”
Section: Intrinsic Motivation / Incentivesmentioning
confidence: 99%
“…In business and marketing, research shows that intrinsic motivation is influenced by idea generation and purchase intention [40,52]. Crowdsourcing as a domain uses intrinsic motivation in several studies, influencing participation, contribution, and worker performance [56,60,63,66]. Other domains that emphasize the effects of motivation are learning [76], computer science [77], sustainability [88], tourism [94], and health [31].…”
Section: Intrinsic Motivation / Incentivesmentioning
confidence: 99%